Practical Considerations for Assessing Pulmonary Gas Exchange and Ventilation During Flume Swimming Using the MetaSwim Metabolic Cart. Issue 7 (July 2019) - Lomax, Mitch; Mayger, Billy; Saynor, Zoe L.; Vine, Christopher; Massey, Heather C.
Abstract : Abstract: Lomax, M, Mayger, B, Saynor, ZL, Vine, C, and Massey, HC. Practical considerations for assessing pulmonary gas exchange and ventilation during flume swimming using the MetaSwim metabolic cart. J Strength Cond Res 33(7): 1941–1953, 2019—The MetaSwim (MS) metabolic cart can assess pulmonary gas exchange and ventilation in aquatic environments. The aims of this study were: (a) to determine the agreement between minute ventilation (VE ), pulmonary oxygen uptake (VO2 ), and carbon dioxide output (VCO2 ) using the MS and Douglas bag (DB) methods during flume swimming; and (b) to assess the repeatability of these and other MS-derived parameters. Sixteen trained swimmers completed a combined incremental and supramaximal verification cardiopulmonary swimming test to determine maximal VO2, 2 progressive intensity swimming tests during which MS and DB measurements were made (agreement protocol), and 3–4 constant-velocity submaximal swimming tests during which only the MS was used (repeatability protocol). Agreement was determined using limits of agreement (LoA), bias, random error, and 95% confidence intervals with systematic bias assessed using paired samples t -tests. Within-trial and between-trial repeatability were determined using the coefficient of variation (CV) and the repeatability coefficient (CR). Where data were heteroscedastic, LoA and CR were log-transformed, antilogged, and displayed as ratios. MetaSwim underestimated peak VO2 and VCO2 (⩽0.39 L·min −1 ) and VE (9.08 L·min −1 ), whereas submaximal values varied between 2 and 5% for CV and ±1.09–1.22 for ratio CR. The test-retest CV during constant-velocity swimming for VE, tidal volume, breathing frequency, VO2, VCO2, and end-tidal pressures of O2 and CO2 was <9% (ratio CR of ±1.09–1.34). Thus, the MS and DB cannot be used interchangeably. Whether the MS is suitable for evaluating ventilatory and pulmonary responses in swimming will depend on the size of effect required.